2008
DOI: 10.1086/591223
|View full text |Cite
|
Sign up to set email alerts
|

The Flattened Dark Matter Halo of M31 as Deduced from the Observed HiScale Heights

Abstract: In this paper, we use the outer-galactic HI scale height data as well as the observed rotation curve as constraints to determine the halo density distribution of the Andromeda galaxy (M31). We model the galaxy as a gravitationallycoupled system of stars and gas, responding to the external force-field of a known Hernquist bulge and the dark matter halo, the density profile of the latter being characterized by four free parameters. The parameter space of the halo is optimized so as to match the observed HI thick… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 28 publications
3
53
0
2
Order By: Relevance
“…D08 found that the halo shape changes by Δ( b / a ) ≳ 0.2 out to at least half the virial radius. This shape change reconciles the strongly prolate‐triaxial shapes found in collisionless N ‐body simulations of the hierarchal growth of haloes (Bardeen et al 1986; Barnes & Efstathiou 1987; Frenk et al 1988; Dubinski & Carlberg 1991; Jing & Suto 2002; Bailin & Steinmetz 2005; Allgood et al 2006) with observations, which generally find much rounder haloes (Schweizer, Whitmore & Rubin 1983; Sackett & Sparke 1990; Franx & de Zeeuw 1992; Huizinga & van Albada 1992; Buote & Canizares 1994; Franx, van Gorkom & de Zeeuw 1994; Kuijken & Tremaine 1994; Bartelmann, Steinmetz & Weiss 1995; Kochanek 1995; Olling 1995, 1996; Schoenmakers, Franx & de Zeeuw 1997; Koopmans, de Bruyn & Jackson 1998; Olling & Merrifield 2000; Andersen et al 2001; Buote et al 2002; Barnes & Sellwood 2003; Debattista 2003; Iodice et al 2003; Oguri, Lee & Suto 2003; Diehl & Statler 2007; Banerjee & Jog 2008).…”
Section: Introductionsupporting
confidence: 77%
“…D08 found that the halo shape changes by Δ( b / a ) ≳ 0.2 out to at least half the virial radius. This shape change reconciles the strongly prolate‐triaxial shapes found in collisionless N ‐body simulations of the hierarchal growth of haloes (Bardeen et al 1986; Barnes & Efstathiou 1987; Frenk et al 1988; Dubinski & Carlberg 1991; Jing & Suto 2002; Bailin & Steinmetz 2005; Allgood et al 2006) with observations, which generally find much rounder haloes (Schweizer, Whitmore & Rubin 1983; Sackett & Sparke 1990; Franx & de Zeeuw 1992; Huizinga & van Albada 1992; Buote & Canizares 1994; Franx, van Gorkom & de Zeeuw 1994; Kuijken & Tremaine 1994; Bartelmann, Steinmetz & Weiss 1995; Kochanek 1995; Olling 1995, 1996; Schoenmakers, Franx & de Zeeuw 1997; Koopmans, de Bruyn & Jackson 1998; Olling & Merrifield 2000; Andersen et al 2001; Buote et al 2002; Barnes & Sellwood 2003; Debattista 2003; Iodice et al 2003; Oguri, Lee & Suto 2003; Diehl & Statler 2007; Banerjee & Jog 2008).…”
Section: Introductionsupporting
confidence: 77%
“…The joint Poisson equation in cylindrical coordinates for an axisymmetric system of stars and gas is given by where φ total is the net potential of the disc due to the stars, the H i gas and the dark matter halo, ρ i with i = 1 to 2 denotes the mass volume density for each of the disc components (stars, gas) while ρ h denotes the same for the halo, and is given by (de Zeeuw & Pfenniger 1988): where ρ 0 is the central core density of the halo, and R c is the core radius, as applicable for a pseudo‐isothermal density distribution. One may note here that since dwarf galaxies have rotation curves that are generally rising out to the last measured point (Salucci et al 2007), the radial term in cannot be ignored as in the case for large spirals with almost flat rotation curves (Narayan et al 2005; Banerjee & Jog 2008).…”
Section: Modelmentioning
confidence: 98%
“…All applications of the flaring method have indicated highly flattened halo distributions with q ≤ 0.5 (Becquaert 1997;Becquaert & Combes 1997;Sicking 1997). Recently, Banerjee & Jog (2008) measured a flattening of q = 0.4 from flaring of the HI layer in M 31. This assumed a constant HI velocity dispersion with radius; if it is allowed to have a modest decline in the outer disk the flattening can be made less with q more like 0.5 to 0.6.…”
Section: Comparison To Other Workmentioning
confidence: 99%